1997
DOI: 10.1128/cdli.4.1.33-42.1997
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of disease progression in long-term experimental feline retrovirus (feline immunodeficiency virus and feline leukemia virus) infections: hematology, clinical chemistry, and lymphocyte subsets

Abstract: After several years of latency, feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) cause fatal disease in the cat. The aim of this study was to determine laboratory parameters characteristic of disease progression which would allow a better description of the asymptomatic phase and a better understanding of the pathogenesis of the two infections. Therefore, experimentally infected cats (FIV and/or FeLV positive) and control animals were observed over a period of 6.5 years under identical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
2
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 55 publications
12
75
2
6
Order By: Relevance
“…Furthermore, FIV infection leads to an impaired humoral and cellular immune response and finally to an AIDS-like syndrome in infected cats (Pedersen et al, 1987;Ishida and Tomoda, 1990;Pedersen and Barlough, 1991). CD4 T lymphocytes progressively decline in FIV-infected cats Torten et al, 1991), but also elevated serum globulin fractions were demonstrated in such animals (Shelton et al, 1995;Hofmann-Lehmann et al, 1997). The FIV-infected cats of the present study had significantly lowered CD4 blood lymphocyte counts (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Furthermore, FIV infection leads to an impaired humoral and cellular immune response and finally to an AIDS-like syndrome in infected cats (Pedersen et al, 1987;Ishida and Tomoda, 1990;Pedersen and Barlough, 1991). CD4 T lymphocytes progressively decline in FIV-infected cats Torten et al, 1991), but also elevated serum globulin fractions were demonstrated in such animals (Shelton et al, 1995;Hofmann-Lehmann et al, 1997). The FIV-infected cats of the present study had significantly lowered CD4 blood lymphocyte counts (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…They were all negative for FeLV p27 antigen by ELISA, and for antibodies to FHV (<1:20), FCV (<1:20), FPV (<1:25), FCoV (<1:25) and FeSFV (<1:25). Cats of group 1 from which FIV had been re-isolated numerous times (Hofmann- Lehmann et al, 1997), were positive for antibodies to TM measured by ELISA, while cats of group 2 were ELISA-negative (Table 1). Cats of group 1 had significantly lower absolute CD4 lymphocyte counts (p0.0025, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These secondary infections frequently become resistant to antimicrobial therapy and eventually result in death (Yamamoto et al, 1989). Long-term survivors have been reported for FIV-infected cats similar to the long-term nonprogressors reported for HIV-positive individuals (Bendinelli et al, 1995;Hofmann-Lehmann et al, 1997). The long-term survivors appear to make up a sizable population of naturally infected pet cats which can survive for many years with minimal clinical disease.…”
Section: Pathogenesis and Infectionmentioning
confidence: 54%